Descriptive Study of Consumption of Food and Health Care of Pregnant Women During the Pandemic in Puskesmas Menganti Gresik - Maramis, Silvi Listiya (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Pregnancy is a process of developing the fetus in the womb until the fetus is mature and ready to be born. One particular group that is vulnerable to the Covid-19 virus is pregnant women. The pandemic period greatly affected access to income to food security, due to the enactment of government policies related to PPKM. This makes it difficult for people to get food, indirectly it is suspected to be a factor causing changes in nutritional practices or fulfilling pregnant women’s nutrition optimally. In addition, during the pandemic there was a change in the frequency of health services for pregnant women. Based on data from visits to pregnant women, the number of pregnant women having ANC examinations has decreased. This study aims to determine the level of adequacy of nutritional intake, food diversity and description of the health care pattern of pregnant women during the pandemic. This research is a quantitative descriptive study with a cross sectional design approach involving 49 pregnant women and the sampling technique was purposive sampling. This research was carried out in the working area of the Menganti Gresik Health Center in August 2021-September 2022. The results showed that pregnant women had mostly good health care patterns but had an adequate level of nutritional intake and food diversity in the less category. This illustrates that good health care patterns have not supported optimal food consumption for pregnant women during a pandemic.